IMPROVING VOCABULARY MASTERY USING PICTURE FOR SECOND GRADE STUDENTS AT SLB- C TUT WURI HANDAYANI - Pipit Pitria Handayani; Imam Muddin (PROJECT (Professional Journal of English Education), 2018)
Communication is always needed in the lifes of human. The human communicate using different language. The language used always has vocabulary to understand. So, the communication can ocuur well. The vocabulary of language is a basis in learning language, includes English as foreign language in Indonesia that learnt by students elementary school untill University. Learning vocabulary of language is not easy especially for the students who has mental retardation. It was proved by the observation at Second Grade of SLB C Tut Wuri handayani that shows that they are low to memorize and difficult to say the vocabulary of English. To solve the problem, the writer conducted the research by using picture media to improve student’s vocabulary mastery. This research used qualitative research design with Classroom Action Research Method. The sample of this reearch was 5 students at second grade. The instrument used was observation then the data collection and analysis was observation. The result of this research shows that the student’s vocabulary mastery in learning english towards Mental retadartion  students at SLB- C Tut Wuri Handayani was improved. Keywords:  Vocabulary, Picture Media